From digital tax symbolism to meaningful reform: Europe's substantial VAT gap as a source of untapped fiscal capacity - Matthias Bauer; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2026)
Europe does not suffer from a lack of tax instruments - it suffers from too many. Over the past decade, new layers of corporate, digital, and global tax rules have been added to an already complex system, often delivering limited revenues while increasing legal uncertainty, compliance costs, and economic distortions. We argue that stronger industrial competitiveness and sustainable public finances will not be achieved through new digital taxes or unilateral corporate tax initiatives, but by strengthening existing tax bases and improving the efficiency, simplicity and predictability of current frameworks. The multilateral approach has delivered some tangible progress, notably by enhancing transparency through country-by-country reporting, even if the full effects of its implementation are still unfolding. That said, further OECD initiatives should be rejected if they risk adding additional layers of complexity without enhancing global coherence or legal certainty. Alongside international coordination, the most promising path lies in domestic tax reform. Governments should prioritise simplification, transparency and the strengthening of broadbased consumption taxes, particularly VAT, which remain the backbone of European public finances. Well-designed domestic reforms can strengthen fiscal resilience, enhance industrial competitiveness by reducing economic distortions and compliance burdens, and enable countries to secure first-mover advantages in an increasingly competitive global environment.
Keywords: 330